2017
DOI: 10.3389/fendo.2017.00326
|View full text |Cite
|
Sign up to set email alerts
|

Saxagliptin Induces β-Cell Proliferation through Increasing Stromal Cell-Derived Factor-1α In Vivo and In Vitro

Abstract: Dipeptidyl peptidase-4 inhibitors, such as saxagliptin, have been reported to have beneficial effects on β-cell function, but the specific underlying mechanism remains unclear. Stromal cell-derived factor-1α (SDF-1α), a chemokine produced in multiple organs, has been considered as a crucial regulator in promoting β-cell survival. Here, we speculate that SDF-1α might mediate the effect of saxagliptin on improving β-cell function. After 12-week saxagliptin treatment in high-fat diet/streptozotocin-induced diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…DPP‐IV can cleave and inactivate SDF‐1, which can then no longer activate CXCR4. In our previous research group studies, we found that compared with non‐diabetic mice, the expression of DPP‐IV in the islets of diabetic mice was enhanced 13 . Therefore, with a diabetic condition, SDF‐1 was abundantly expressed in pancreatic tissues, but the number of islets β cells undergoing dedifferentiation was not reduced.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…DPP‐IV can cleave and inactivate SDF‐1, which can then no longer activate CXCR4. In our previous research group studies, we found that compared with non‐diabetic mice, the expression of DPP‐IV in the islets of diabetic mice was enhanced 13 . Therefore, with a diabetic condition, SDF‐1 was abundantly expressed in pancreatic tissues, but the number of islets β cells undergoing dedifferentiation was not reduced.…”
Section: Resultsmentioning
confidence: 88%
“…SDF‐1 is associated with the mediation of islet β cells function. For example, our previous study found that the DPP‐IV inhibitor Saxagliptin improved the function of islet β cells through regulating SDF‐1 expression 13 . Another study also revealed the important role of SDF‐1 in β cells survival after islet transplantation 14 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The reason for this discrepancy between clinical observations and experimental studies is due to the methodological differences in SDF-1α assays. In addition, experimental studies have shown that a DPP-4 inhibitor significantly increased SDF-1α levels in a murine model of type 1 diabetes 34,35 . Further studies in which the relationship between effects of DPP-4 inhibitors on SDF-1α levels is evaluated in a murine model of type 2 diabetes may reveal the reason for this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…We matched the cases and control for BMI and adjusted all factors against BMI in cox regression analysis. This could be explained by activation of hematopoietic stem cells in response to DPP4 inhibitors which control inflammatory and immune response pathogenesis of T2DM [13], in association with β-cell regeneration [14].…”
Section: Discussionmentioning
confidence: 99%